Applications of Nanotechnology in Material Science - Hmoud, Walid Khaled; Gharkan, Jaafar Adnan; Hamed, Weldan Saad; Jader, Miami Hameed; Mohammed, Aya Jassim (American Journal of Botany and Bioengineering, 2024)
Nanotechnology has opened new avenues in the field of material science. The introduction of a small amount of nanomaterials often leads to beneficial modification of the physical, mechanical, thermal, electrical, and optical properties of bulk materials. It leads to the development of new classes of materials termed nanocomposites and multifunctional materials. Nanotechnology has promising applications in both structural materials used in packaging, transportation, housing, and communication, and functional materials used in coatings, healthcare, electronics, electromechanical systems, functional fluids, and as catalysts. Some of the applications are multifunctional windows and seals, neutron-absorbing hexagonal boron nitride coating to limit radiation, microprocessor application of yttrium-barium-copper-oxide superconductor, sinter-resistant dispersible nanocatalysts, nanocatalyst blocks for hydrogen generation, and minimal radiation fibula screws and implants. Applications of nanotechnology can be seen under the following heads: 1.1. Structural Materials: Primary applications of nanotechnology can be viewed in our day-to-day life in terms of materials used in structural applications. Nanotechnologically modified materials can show an improvement in the properties and lead to a disproportionate improvement in the lifetime compared to bulk materials. 1.2. Functional Materials: These materials can be used either in the form of bulk or as films or coatings. Functional materials refer to the materials that have very high functionality and work at the nanoscale. A major concern in the preparation of the materials is the sustainability of the process and the life of coated materials in service.